Fostering Patriotism Through National Songs in Elementary Education: Menumbuhkan Patriotisme Melalui Lagu Nasional di Pendidikan Dasar - Anthonio Dion Purwoadi; Vanda Rezania (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Character education is crucial for developing patriotism in students, particularly within Indonesia's Merdeka Curriculum. Gap: The effectiveness of using national songs to foster love for the motherland remains underexplored. Aim: This study examines the role of national songs in promoting patriotism among Grade 5 students at SDN Wunut II Porong. Results: Regular singing of national songs, coupled with understanding their lyrics, enhanced students' nationalist behaviors, though some struggled with unfamiliarity and inconsistent practices. Novelty: It highlights the practical use of daily singing routines in character education. Implications: Structured activities like this can strengthen national identity in schools implementing similar curricula. Highlights: Singing national songs fosters patriotism by integrating daily routines with character education. Understanding song lyrics enhances students’ appreciation of national identity and values. Regular practice promotes consistent nationalist behaviors despite initial challenges. Keywords: Character Education, Patriotism, Merdeka Curriculum, National Songs, Elementary Students